PENGARUH MODEL PEMBELAJARAN INKUIRI BERBANTUAN MEDIA ASSEMBLR EDU TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Bintang Muhibuttobari Suparman; Puji Rahayu; Nenden Permas Hikmatunisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this study is the low critical thinking skills of elementary school students. Therefore, this study aims to determine the effect of the Assemblr Edu media-assisted inquiry learning model on improving students' critical thinking skills and also to determine the improvement of critical thinking skills in students who get the application of the Assemblr Edu Media-assisted Inquiry Learning Model better than students who get the application of the Student Team Achievement Division (STAD) type cooperative learning model. This research used experimental method with quasi experimental design in the form of nonequivalent control group. The samples in this study were VC and VD grade students in one of the elementary schools in Purwakarta Regency which were divided into experimental and control groups. The experimental group used the inquiry learning model assisted by Assemblr Edu media, while the control group used the STAD type cooperative learning model. The instrument used was a critical thinking skills test given before and after treatment. The results of data analysis showed that the coefficient of determination was 35%. The N-Gain score for the experimental class was 0.4221 (Medium), while the control class was 0.2038 (Low). Based on the results of the data analysis, it can be concluded that the inquiry learning model assisted by Assemblr Edu media has an effect and increases the ability to think critically.